Synthesis of defect graphene and its application for room temperature humidity sensing - Huang, Qingwu; Zeng, Dawen; Tian, Shouqin; Xie, Changsheng (Materials letters, 2012)
Defect graphene was reported by adding sugar through solvothermal method. The characterization results of XRD, IR, Raman, and XPS showed that the samples have tunable mount of oxygenated group, which plays a role as adsorption site to detecting humidity gas molecule. The sample from sucrose has the highest mount of functional oxygenated groups and shows the best humidity property. ► Graphene with tunable defect was reported through solvothermal method. ► The defect was considered as oxygenated groups based on characterization results. ► The sample from sucrose has the most mount of functional oxygenated groups. ► The defect plays a role as adsorption site to detecting humidity gas molecule. ► The sample from sucrose shows the best humidity property.